2012
DOI: 10.1089/ten.tea.2011.0375
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Amelogenin Peptides on Osteogenic DifferentiationIn Vitro: Identification of Possible New Drugs for Bone Repair and Regeneration

Abstract: Enamel matrix proteins (EMP) have been shown to promote regeneration of periodontal ligament and root cementum, and sometimes to enhance the differentiation of bone-forming cells in vitro and new bone growth in vivo. However, the inconsistent and unpredictable effects of EMP that have been reported for bone regeneration may be due to the highly variable composition of this heterogeneous material, which is comprised mainly of amelogenin and amelogenin-derived peptides. The present study has therefore examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…Previous studies on the effects of EMD, conducted on a variety of research models, have been inconclusive (21,22). A number of ambiguities have made it hard to compare the results between studies and have impeded the characterization of the functions of the different components of EMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the effects of EMD, conducted on a variety of research models, have been inconclusive (21,22). A number of ambiguities have made it hard to compare the results between studies and have impeded the characterization of the functions of the different components of EMD.…”
Section: Discussionmentioning
confidence: 99%
“…A number of ambiguities have made it hard to compare the results between studies and have impeded the characterization of the functions of the different components of EMD. Firstly, previous in vitro studies have used various cell types (epithelial, tongue carcinoma, gingival fibroblast, periodontal ligament, bone marrow-mesenchymal stem cells) obtained from different species (such as, rat, pig and human) (18,19,2124). Secondly, the studies used a number of different EMPs, such as commercial lyophilized EMD and different fractions isolated from it (<6 kDa, mainly TRAP; >6 kDa, LRAP, sheathing peptides and the full-length AMEL) (21), or numerous recombinants, such as full-length AMEL (22) and chemically synthesized 5.3 kDa TRAP (23).…”
Section: Discussionmentioning
confidence: 99%
“…Spahr, 2006 [36]; Haze, 2009 [8]; Iizuka, 2011 [18]; Tamburstuen, 2011 [10]; Atsawasuwan, 2013 [40], 4. Matsuzawa, 2009 [59]; Iizuka, 2011 [18]; Tamburstuen, 2010 [42]; Amin, 2013 [64]; Atsawasuwan, 2013 [24], 5. Haze, 2009 [8]; Tamburstuen, 2011 [10], 6.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the synthetic fragment of the amelogenin peptide (TRAP) (45 amino acids N-terminal) did not promote wound healing. Stout et al [41] did not find biologic activity for TRAP, and Amin et al [42] found its suppressive effect on periodontal ligament and alveolar bone. TRAP seems not to participate in stimulation of both gingival epithelial cells and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%